High-Performance Thin PTFE-Ni Metamaterial Absorber for Ultra-Broadband Applications - Camilla C. Moro Carmo; Ursula C. Resende; Silvia C. Albuquerque; Mauricio D. Almeida (IEEE Access)
This study presents a high-performance, ultra-thin metamaterial absorber consisting of nickel resonator disks arranged in a $4× 4$ matrix on a polytetrafluoroethylene (PTFE) substrate. The novelty of the design lies in the integration of nickel—a cost-effective alternative to noble metals—and PTFE, whose excellent thermal stability enhances the overall performance of the metamaterial. Additionally, the simplified unit cell structure enables scalability and offers a practical alternative to conventional absorbers. The proposed metamaterial absorber achieves broadband absorption across the ultraviolet, visible, and infrared spectra. A systematic parametric analysis was conducted to optimize the structural parameters, maximizing absorption efficiency while maintaining minimal thickness. Numerical simulations performed in CST Studio Suite validated the optimized design, demonstrating an average absorption of 99.00% and a peak absorption of 99.36% within the $375-850$ nm range. Given the elevated absorption rates achieved, the analysis range was extended to $300-3000$ nm, and a genetic algorithm was employed to refine the geometric parameters. This optimization resulted in a stable absorption profile with an average efficiency of 98.98%, and a peak of 99.96%. This structurally simple design offers an advantage by combining cost-effective material selection with high broadband absorption performance.